PENGARUH INTELLECTUAL CAPITAL, UKURAN PERUSAHAAN, CSR, DAN STRUKTUR KEPEMILIKAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Agam Mei Yudha (Journal of Information System, Applied, Management, Accounting and Research, 2021)
This study aims to determine how much influence Intellectual Capital, Company Size, Corporate Social Responsibility (CSR), and Ownership Structure have on the Company's Financial Performance in Manufacturing Companies Listed on the IDX in 2015-2019 . This study uses secondary data. The method used in this research is pane l data regression analysis . This study used 34 manufacturing companies listed on the IDX from 2015 to 2019 which were used as samples. The sample technique in this study used purposive sampling, namely the determination of the sample using certain criteria. Data processing is done with tools Eviews. From this research, the following conclusions are obtained: (1) There is a positive and significant influence between Intellectual Capital and Financial Performance . (2) There is a positive and significant influence between Company Size on Financial Performance . (3) There is a negative and significant influence between Corporate Social Responsibility on Financial Performance . (4) There is a negative and significant influence between Ownership Structure on Financial Performance . (5) There is a positive and significant influence between Intellectual Capital , Company Size, Corporate Social Responsibility, and Ownership Structure simultaneously on financial performance.